STYLE DIRECTION "UNISEX" AS A DESIGN PRACTICE IN FASHION DESIGN - Chuprina, N. V.; Paranko, N. P.; Prasol, S. I.; Baranova, A. I.; Kovalchuk, M. O.; Omelchenko, H. V. (Art and Design, 2021)
The study is devoted to defining the basic principles of formation of the style direction "unisex" as a design practice of fashion design; the formulation of generalized image-design characteristics of this style direction for the development of costume collections as a relevant fashion product for mass consumption. Methodology of research is based on a comprehensive approach to identifying image-design and artistic-compositional properties of costume collection development, in particular methods of socio-cultural analysis, historical and logical development, system-structural, comparative, compositional and stylistic analysis. At separate stages methods of morphological analysis and synthesis, sociological interrogation are applied. The origin of the "unisex" style direction, its features, the obligatory compositional elements in fashion design, the evolution of form, the main elements of products in the style of "unisex" are studied. The stylistic direction of "unisex" is characterized from the standpoint of assimilation of interactive development of men's and women's costume of the twentieth century. The systematization of figurative-design and constructive-compositional features of the main substrates of the style direction "unisex" in the modern market of fashionable clothes of general purpose is carried out. It is identified and characterized the artistic and compositional features of the collection of modern women's clothing in the stylistics of "unisex", taking into account modern materials. The general features of the collection models are systematized and the elements characteristic of the "unisex" style direction, which are the basis for designing the author's collection of women's clothing are structured. The author's collection of women's clothing, corresponding to the tendencies of the "unisex" style direction, has been designed. The scientific novelty of the study is to determine the image-design properties of the style direction "unisex" as a design practice in modern fashion design for mass consumption. The degree of aesthetics of the ideological content and gender aspects of the image-project of "unisex" phenomenon in the modern cultural and artistic space is determined. The main elements of the suit, which interactively interact with the design of men's and women's clothing as a fashion product, have been identified. The practical significance of the study of the main design characteristics of the application of the style direction of "unisex" in clothing design is determined by commercial potential, which allows fashion designers in the mass market segment and clothing brands to reduce production costs and further promotion: a single design, collection for men and women from the same materials, general advertising, etc.